2016
DOI: 10.1590/s1984-4689zool-20150075
|View full text |Cite
|
Sign up to set email alerts
|

Carbon primary sources and estuarine habitat use by two congeneric ariid catfishes in a subtropical coastal lagoon

Abstract: ABSTRACT. Although ariid catfishe species are known to use coastal systems during some stages of their life cycles, the energetic contribution of estuarine resources and habitat use by many species in this family are still unclear. We used stable isotope analyses to estimate the assimilation of primary carbon sources and to infer the use of estuarine and freshwater habitats by two ariid catfishes Genidens barbus (Lacepède, 1803) and Genidens genidens (Cuvier, 1829). An isotopic mixing model revealed that juve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…(2016). This age corresponds to the early months of life that occur between the fresh water or estuary, where the species spawns (Reis, 1986b; Araújo, 1988; Pereyra et al ., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…(2016). This age corresponds to the early months of life that occur between the fresh water or estuary, where the species spawns (Reis, 1986b; Araújo, 1988; Pereyra et al ., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Pereyra et al . (2016) found that G. genidens adults consumed freshwater-derived carbon sources, and Bizerril (1999) also observed spatial differences governed by salinity in the habitat usage of marine catfishes, allowing their coexistence. The stable isotopes of the present study revealed no variation in habitat usage.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the Ariidae family is represented by demersal marine catfishes usually found in coastal and estuarine ecosystems (Marceniuk & Menezes, 2007; Schmidt et al ., 2008; Denadai et al ., 2012; Pereyra et al ., 2016). Along the coast of São Paulo and Rio de Janeiro, their spatial distribution in estuarine systems is governed by salinity (Bizerril, 1999; Denadai et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…competition and/or predation pressure) experienced by each individual fish within the population (Chapman et al ., 2012 b ). We speculate that some individuals of G. genidens may seek freshwater reaches of the Patos Lagoon to ameliorate interspecific competition with the congeneric species G. barbus and G. planifrons (Araújo, 1988), which also use the estuarine zone of this lagoon as feeding grounds (Araújo, 1984; Pereyra et al ., 2016). Partial migration and the occurrence of contingents were also reported for the congeneric marine catfish G. barbus , in the adjacent La Plata River, Argentina and south Brazil (Avigliano et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%